Influência de um programa de exercícios do método Pilates sobre a massa óssea de idosas sedentárias - Liposcki, Daniela Branco (2016)
Introduction: With aging changes occur in the bone tissue, both as fast resorption as bone formation, decrease the accumulation of plastic deformation and micro damages, leaving it more prone to fracture bone. These changes may significantly affect the health of the elderly. The Pilates exercises may eventually contribute to the improvement of these characteristics, but despite the growing number of professionals who use the Pilates principles studies are needed to investigate the effectiveness of the technique and its clinical application. Purpose: To verify the effects of a Pilates program on bone mass and body composition in elderly, sedentary. Method: Blind controlled clinical trial which included a sample of 24 sedentary elderly women living in the city of Lages / SC, divided into two groups: GP (Pilates Group) and CG (Control Group). The GP held a Pilates exercise program (mat and equipment) 2 times a week for 6 months. Bone densitometry (DXA) was used to assess bone mineral density (BMD) of the participants before and after the intervention. This research was approved by the Research Ethics Committee (CEP) of the Pontifical Catholic University of Rio Grande do Sul (PUCRS) and registered in the Brazilian Registry of Clinical Trials (Rebec). For the statistical analysis SPSS 20.0 for Windows 8 was used. For the analysis of normality Shapiro-Wilk was used; fot infer the T-Student test was used for normal distribution, and the Mann-Whitney U test for asymmetrical distribution, with significance level set at 5% (p<0.05). Results: 20 elderly women were reevaluated, 9 (63.7 ± 3.3 years old) from the GP and 11 (65.2 ± 3.0 year olds) from the GC. After the intervention there was no significant difference in lumbar BMD (p = 0.14), femoral neck (p = 0.57) and total hip (p = 0.52) between groups. There was a correlation (r = 0.87) proportional between the body mass index (BMI) and BMD. A significant decrease was found (p = 0.03) in the abdominal circumference of the GP. Although not statistically significant, there was improvement in aspects related to the percentage of body fat and lean tissue in GP. Conclusion: A Pilates exercise program held twice a week for six months showed no significant changes in BMD of the investigated elderly.